A novel un-doped long lasting phosphorescence phosphor： SrZrSi2O7 - 李晓晨 邹泽华 王治龙 武传强 张加驰 王育华 (Journal of rare earths, 2015)
A novel phosphor of un-doped Sr Zr Si2O7 material with blue long lasting phosphorescence which could be recorded for about 5400 s（0.32 mcd/m^2） was developed. It revealed that both the emission centers and traps levels were related to the oxygen-deficient defects which were induced in reducing atmosphere. The filling and fading experiments indicated that the traps levels in Sr Zr Si2O7 were continuous in distribution. The influence of shallow traps on deep traps was investigated and the important role of the bridge effect was revealed. The un-doped Sr Zr Si2O7 material obtained in reducing atmosphere showed potential application as a cheap blue long lasting phosphorescence phosphor.